Posttraumatic Meningitis Due to Hemophilus Influenzae Type a - Leblanc, Wiener (1983)
Posttraumatic meningitis is uncommon in children. This case report describes a 4-year-old child with this complication caused by an unusual type of Hemophilus influenzae. The efficacy of routine use of antibiotics in preventing posttraumatic meningitis remains uncertain. However, this report suggests that in the presence of prolonged fever and clinical evidence of a dural tear, antibiotic treatment is warranted.